Accelerating O‐Redox Kinetics with Carbon Nanotubes for Stable Lithium‐Rich Cathodes. Issue 7 (19th May 2022) - Zhou, Junhua; Chen, Zhujie; Yu, Guo; Ma, Keni; Lian, Xueyu; Li, Shuo; Shi, Qitao; Wang, Jiaqi; Guo, Lingli; Liu, Yu; Bachmatiuk, Alicja; Sun, Jingyu; et al.
Abstract: Lithium‐rich cathodes (LRCs) show great potential to improve the energy density of commercial lithium‐ion batteries owing to their cationic and anionic redox characteristics. Herein, a complete conductive network using carbon nanotubes (CNTs) additives to improve the poor kinetics of LRCs is fabricated. Ex situ X‐ray photoelectron spectroscopy first demonstrates that the slope at a low potential and the following long platform can be assigned to the transition metal and oxygen redox, respectively. The combination of galvanostatic intermittent titration technique and electrochemical impedance spectroscopy further reveal that a battery with CNTs exhibited accelerated kinetics, especially for the O‐redox process. Consequently, LRCs with CNTs exhibit a much better rate and cycling performance (≈89% capacity retention at 2 C for over 200 cycles) than the Super P case. Eventually, TEM results imply that the improved electrochemical performance of the CNTs case also benefits from its more stable bulk and surface structures. Such a facile conductive additive modification strategy also provides a universal approach for the enhancement of the electron diffusion properties of other electrode materials. Abstract : Stable lithium rich cathode (≈89% capacity retention at 2 C for over 200 cycles) is deveolped via forming a complete CNTs conductive network, contributing to its accelerated O‐redox and enhanced structural stability.